Eksplorasi Etnomatematika pada Situs Watu Gudig - Restu Hayyu Khoirunnisa; Dafid Setiana; Denik Agustito (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
This research was conducted to review the mathematical elements contained in the cultural heritage building of the Watu Gudig Site (ethnomathematics). This research uses descriptive qualitative research methods with an ethnographic approach. To obtain accurate data, it is done by observing, interviewing and researching archives. Observations were made to determine the mathematical elements contained in the Watu Gudig Site. Interviews were conducted to obtain cultural aspects of the Watu Gudig Site. Archival research was carried out by triangulation technique, which means analyzing data from different sources to support the data that has been obtained from observations and interviews. The results of this research are found the concept of plane geometry in the cultural heritage building of Watu Gudig Site. The geometric concepts contained in this building are in the form of a square, trapezoid, rectangle, and block.